The impact of classroom acoustic environments on the behaviour of special needs students: a systematic literature review - Aziz Azwan Karim; Khairul Farhah Khairuddin (Penerbit Universiti Kebangsaan Malaysia, 2025)
This systematic literature review explores the impact of acoustic environments on the behaviour of special needs students, addressing a crucial gap in understanding how poor classroom acoustics affect learning and well-being. Despite growing awareness of inclusive education, limited research consolidates how optimized acoustic conditions can support behavioural and educational outcomes for this group. To address this, a structured review of articles published between 2021 and 2024 was conducted using Scopus and Web of Science. Inclusion criteria included English-language journal articles, within the final publication stage, in the social sciences domain. The review adhered to the PRISMA framework, resulting in 24 relevant studies for final analysis. Two main themes emerged: (1) the importance of acoustic quality in educational settings, and (2) strategies to improve classroom acoustic environments. The findings underscore the need for targeted interventions to create acoustically supportive classrooms that meet the cognitive, emotional, and behavioural needs of special needs students. This study offers critical insights for educators and policymakers, emphasizing that poor acoustics can heighten learning challenges. It calls for urgent revisions in educational policies, inclusive classroom designs, and implementation of evidence-based acoustic modifications to ensure equitable learning opportunities for all students, particularly those with special needs.